β-N-acetylhexosaminidase: what's in a name…? - Slámová, Kristýna; Bojarová, Pavla; Petrásková, Lucie; Kren, Vladimír (Biotechnology advances, 2010)
β-N-acetylhexosaminidases (EC 3.2.1.52, belonging to CAZy GH families 3, 20 and 84) have recently gained a lot of attention, not only due to their implication in human physiology and disease, but also due to their great potential in the enzymatic synthesis of carbohydrates and glycomimetics. GH family 20 β-N-acetylhexosaminidases, and GH family 3 and 84 β-N-acetylglucosaminidases from all kinds of organisms have been intensively studied from the point of view of their physiological roles, reaction mechanisms, structure and inhibition. Thanks to their outstanding substrate promiscuity, extracellular β-N-acetylhexosaminidases from filamentous fungi are able to cleave and transfer substrates bearing various functionalities, ranging from carboxylates, sulfates, acylations to azides, and even 4-deoxy glycosides. Thus, they have proved to be versatile biosynthetic tools for the preparation of both natural and modified hexosaminides under mild conditions with good yields.
Keywords: biokatalýza; beta-N-acetylhexosaminidasy; Biocatalysis; substrátová specifita; Animals; lidé; Enzyme Inhibitors; inhibitory enzymů; Substrate Specificity; zvířata; Humans; beta-N-Acetylhexosaminidases